"We're One Team": Examining Community School Implementation Strategies in Oakland - Kendra Fehrer; Jacob Leos-Urbel (MDPI AG, 2016)
The community school model posits that the traditional school model is not sufficient to overcome the role of poverty in equitable access to learning, and that improving student achievement requires addressing the needs of the whole child. By leveraging community partnerships to address student barriers to learning and shift relationships between schools, families, and community, the community school model represents an expanded vision of what schools are, who they include, and what they are responsible for. This paper aims to improve our understanding of community school implementation, based on qualitative research in five community schools in Oakland, California. We apply the Children's Aid Society's framework of four community school capacities including: (1) comprehensiveness; (2) collaboration; (3) coherence; and (4) commitment (Lubell, 2011) in our analysis. We find evidence of a collaborative culture, in which school and community partner staff worked together across traditional boundaries to serve students. Schools showed signs of coherence of vision and goals, and alignment of services and supports with the instructional core of the school. Community school strategies not only provided important school-based services but also represented an expansion of the traditional school model by leveraging and aligning community partners to improve student outcomes.